2014
DOI: 10.1186/1476-4598-13-220
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 and miR-145 synergistically regulate ERBB3 to suppress cell proliferation and invasion in breast cancer

Abstract: IntroductionERBB3, one of the four members of the ErbB family of receptor tyrosine kinases, plays an important role in breast cancer etiology and progression. In the present study, we aimed to identify novel miRNAs that can potentially target ERBB3 and their biological functions.MethodThe expression levels of miR-143/145 and target mRNA were examined by relative quantification RT-PCR, and the expression levels of target protein were detected by Western blot. We used bioinformatic analyses to search for miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 29 publications
7
106
2
Order By: Relevance
“…miR-100 has been reported to inhibit tumorigenesis in oral squamous cell carcinoma, ovarian cancer and breast cancer by interfering with proliferation and survival signaling (24)(25)(26). Additionally, miR-143 and miR-145 have been observed to synergistically regulate v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 3 to suppress cell proliferation and invasion in breast cancer (27). Moreover, miR-197 and miR-21 were noted to be prominently upregulated in male breast cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…miR-100 has been reported to inhibit tumorigenesis in oral squamous cell carcinoma, ovarian cancer and breast cancer by interfering with proliferation and survival signaling (24)(25)(26). Additionally, miR-143 and miR-145 have been observed to synergistically regulate v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 3 to suppress cell proliferation and invasion in breast cancer (27). Moreover, miR-197 and miR-21 were noted to be prominently upregulated in male breast cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Bischoff et al found that miR-148b, miR-149, miR-326, and miR-520a-3p directly reduced HER3 mRNA and protein levels. 85 Yan et al 92 provided insights into the role of the miR-143/145 cluster as a tumor suppressor in breast cancer; that is, they suggested that it inhibits HER3 translation in vivo. Yu et al 93 suggested that miR-148a attenuates angiogenesis by inhibiting HER3.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%